Green ternary composite of graphitic carbon nitride/TiO2/ polyorthoanisidine for the enhanced photocatalytic treatment of Direct Red 28 for industrial water treatment solutions - Alkorbi, Ali S.; Gill, Nouman; Anjum, Muhammad Naveed; Saif, Muhammad Jawwad; Ahmad, Mirza Nadeem; Qadir, Muhammad Bilal; Khaliq, Zubair; Faisal, Mohd; Jalalah, Mohammed; Harraz, Farid A. (Frontiers in Chemistry, 2024)
Industrial dye effluent causes significant risks to the environment. The present study was focused on photocatalytic degradation of direct dye 28 using a ternary composite of graphitic carbon nitride, TiO2, and polyorthoanisidine (g-C3N4/TiO2/POA), prepared by in-situ oxidative polymerization o-anisidine. The synthesized composite g-C3N4/TiO2/POA properties were characterized using different analytical techniques. X-ray diffraction (XRD) results revealed the prominent pattern of TiO2 and g-C3N4 in composite peak at 2θ° while Fourier transform infrared (FTIR) results provided the confirmation peaks for g-C3N4/TiO2/POA, as well as POA at 1110 cm-1 and 1084 cm-1 for C-O-C ether. Scanning electron microscopy (SEM) demonstrated an increase in the average size of the composite up to 428 nm. Energy dispersive X-ray spectroscopy (EDX) spectrum provided the weight percentages of the C, O, and Ti in the composite were 8.5 %, 45.69 %, and 45.81 %, respectively. The photocatalytic degradation of Direct Red 28 dye under UV irradiation using composite showed that 86 % Direct Red 28 dye was degraded by 30 mg/L dose of g-C3N4/TiO2/POA in 240 minutes at 2 pH. After four consecutive cycles, the utilized composite showed 79% degradation of Direct Red 28, demonstrating the stability and effectiveness of the g-C3N4/TiO2/POA photocatalyst. The high reusability and efficiency of the g-C3N4/TiO2/POA composite are due to increased light absorption range and reduced e-/h+ recombination rate in the presence of g-C3N4 and POA.